The FACTORS AFFECTING INFORMATION TECHNOLOGY SKILLS OF STUDENTS SPECIALIZING ACCOUNTING - AUDITING (International Journal of Scientific Research and Management (IJSRM), 2023)
As we all know, the 4th industrial revolution (Industry 4.0) has brought many great applications to all areas of society. Therefore, it can be seen that mastering information technology (IT) skills will help improve work efficiency, reduce costs, increase global cooperation, thereby gaining competitive advantages (Mamahani, 2006). IT skills are not only important for worker, but also for students, this is one of the necessary skills. The objective of this study is to find out the current situation and evaluate the application of IT skills of students majoring in accounting and auditing at the university of economics in Hanoi in order to meet Industry 4.0, through a survey of 200 students and applying the method of calculating the mean value, the researchers has shown the influence of the factors. This is also the basis for the researchers to propose some recommendations to help students majoring in accounting - auditing improve and enhance their IT skills to create a convenient learning environment as well as open up job opportunities in the future.